Antibacterial efficacy of quaternary ammonium compounds (QACs) against Enterococcus faecalis in endodontic infections: a systematic review and meta-analysis - Ranjeet Ajit Bapat; Sumaiya Zabin Eusufzai; Zohaib Akram; Tanay Chaubal; Khoo Suan Phaik; Liang Lin Seow; Umer Daood (BMC Oral Health)
Abstract Background This systematic review aims to assess the antibacterial efficacy of Quaternary Ammonium Compounds (QACs) against Enterococcus faecalis (E. faecalis) as a root canal irrigant for endodontic infections. Materials and methods A comprehensive literature search was conducted utilizing the databases PubMed, Scopus, Cochrane library and Google Scholar for papers from January 2000 up until January 2024. The research question was formulated using the PICO (Population, Intervention, Control and Outcomes) framework. This review focused on the efficacy of QACs (intervention) against E. faecalis (population) and compare it with NaOCl (comparator 1) and CHX (comparator 2) for antibacterial activity by using findings of colony forming unit (CFU) and confocal laser microscopy (CLSM) (outcomes). A methodological quality assessment was conducted using a scoring methodology provided by Quin tool to evaluate the studies, and the risk of bias was examined. A systematic screening of the selected publications was performed based on predefined inclusion criteria to identify studies eligible for meta-analysis. Results Nine research studies papers included varied in their design and had a low to medium risk of bias. The findings demonstrated a decrease in the number of E. faecalis bacteria following the inclusion of QACs, leading to improved disinfection and efficacy in combating root canal infections. Furthermore, the meta-analysis findings indicated that there was no statistically significant distinction (p > 0.05) in the efficacy of QACs [Quaternary ammonium silane (K21) and Benzalkonium chloride (BAK)] when compared to commercially available NaOCl, however these QACs showed high efficacy against E. faecalis. Conclusion This review found QACs to be promising alternatives to NaOCl and CHX for E. faecalis elimination, though no significant difference was observed in meta-analysis due to study heterogeneity. Standardized in vivo studies are needed for validation. Prospero registration no CRD42023389258. Clinical trial number not applicable.